PENDIDIKAN BERPUSAT PADA ANAK DI KELURAHAN PALEBON - Wiwik Kusdaryani; Dwi Prasetiyawati D.H; Mila Karmila; Peuwadi . (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2014)
Abstract Community Service Event was held with the theme "IBM Child-Centered Education in?é?á Palebon". This activity is done with 3 different kinds of activities, namely 1) the extension of child-centered education; 2) a general description of child-centered curriculum; 3) examples of activities centered learning strategies in children. The training was held on 28 February to 2 March 2014 held at the Village Palebon with a team of resource persons PG-PAUD Teachers' Training College Lecturers IKIP PGRI Semarang. Participants of this activity is early childhood educators in the Village Palebon. While this activity is the application of early childhood educators in District Pedurungan able to create a child-centered learning. The main objective of this activity are?é?á?é?á?é?á : 1). Providing information about the child-centered education; 2). Provide an overview of child-centered curriculum; 3). Provide examplesof activities centered learning strategies in children. Keywords: Child-Centered Education, Early Childhood